Balancing cognitive and environmental constraints when deciding to switch tasks: Exploring self-reported task-selection strategies in self-organised multitasking. Issue 4 (April 2021) - Mittelstädt, Victor; Schaffernak, Insa; Miller, Jeff; Kiesel, Andrea
We investigated how people balance cognitive constraints (switch costs) against environmental constraints (stimulus availabilities) to optimise their voluntary task switching performance and explored individual differences in their switching behaviour. Specifically, in a self-organised task-switching environment, the stimulus needed for a task repetition was delayed by a stimulus-onset asynchrony (SOA) that increased with each consecutive repetition until a task switch reset the SOA. As predicted, participants switched tasks when the SOA in task switches approximately matched their individual switch costs and thus they optimised local task performance. Interestingly, self-reports (confirmed by behavioural switching patterns) revealed two individual strategies: some participants ( N  = 34) indicated to guide their task selection behaviour based on preplanned task sequences over several trials, whereas others ( N  = 42) indicated to primarily decide on a trial-by-trial basis whether to switch or to repeat tasks. Exploration of switching behaviour based on the two strategy groups revealed additional insights into how people achieved adaptive task selection behaviour in this task environment. Overall, the present findings suggest that individuals select tasks with the aim of improving task performance when dealing with multiple task requirements, but they differ in their preferred individual task selection strategies.